2019
DOI: 10.1002/ceat.201800474
|View full text |Cite
|
Sign up to set email alerts
|

Organic Additives for the Enhancement of Laminar Flow in a Brain‐Vessels‐Like Microchannel Assembly

Abstract: Organic polymers were extracted from okra, aloe vera, and hibiscus leaves and used as drag-reducing additives (DRAs) to enhance the laminar flow in custommade microchannels that simulate the human brain vessels. The experiment was conducted using an open-loop microfluidic system. The flow enhancement performance was evaluated as the function of percentage of flow increment of mucilage additives at different concentrations. Okra mucilage showed greater flow enhancement performance at higher mucilage concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The microreactor consisting of a T-junction functioned as a droplet generator as this geometry is one of the most straightforward structures by generating droplets hydrodynamically at the intersection. The microreactor's height was 100 mm which was fabricated by the direct writing method reported in [45,50,51].…”
Section: Microreactor Fabricationmentioning
confidence: 99%
“…The microreactor consisting of a T-junction functioned as a droplet generator as this geometry is one of the most straightforward structures by generating droplets hydrodynamically at the intersection. The microreactor's height was 100 mm which was fabricated by the direct writing method reported in [45,50,51].…”
Section: Microreactor Fabricationmentioning
confidence: 99%
“…Ling et al fabricated PDMS microchannels simulating brain [49] and heart vessels [50][51][52], respectively, to investigate the flow enhancement performance using extracted natural mucilage as additives. The studies demonstrated that at a low concentration of polymeric additives remarkable flow enhancement was achieved, and the results showed the potential organic polymers in enhancing the blood flow, thus being an alternative treatment for certain vascular diseases.…”
Section: Introductionmentioning
confidence: 99%